The impact of water resource constraints on industrial linkages in the Yellow River basin - Lili, Rong; Yanlei, Duan; Shurong, Duan (Frontiers in Environmental Science, 2024)
[Purpose] Low water resources utilization rate, water environment pollution and water ecology deterioration are the unfavorable factors restricting the high-quality development of the Yellow River Basin and the coordinated development of the region, and industrial linkage is an important mechanism to promote the regional "pole-diffusion" effect. Currently, the water resources constraints of the Yellow River Basin are close to the upper limit, in this context, how to enhance the industrial linkage between regions, promote the coordinated development of resources and economy in the Yellow River Basin, and construct new "growth poles" of high-quality development has become an important proposition. [Methods] By analyzing the mechanism of water resource constraints affecting industrial linkage and constructing a mediation effect model, we investigate the transmission mechanism of water resource constraints affecting industrial linkage through virtual water trade and optimization of industrial structure. [Results] The results show that water resource constraints significantly inhibit the development of industrial linkage in the whole basin, but enhance the development of industrial linkage through the promotion of virtual water trade and optimization of industrial structure; in terms of subregions, there are differences in the mediation effect in the Yellow River Basin in the regions. [Marginal contribution] The article analyzes the impact of water resource constraints on the industrial linkage of the regions with advantages in agriculture and animal husbandry, energy industry, and emerging industry & advanced manufacturing industry from the perspective of the adaptability of water resources to the layout of productive forces, and puts forward the proposal of coordinating the linkage development of industries in the whole river basin, which promotes the research on the relationship between water resources and industries.